2013
DOI: 10.1038/pr.2013.74
|View full text |Cite
|
Sign up to set email alerts
|

Impaired lipopolysaccharide responsiveness of cord blood mononuclear cells and the risk of asthma: a longitudinal study

Abstract: Background:We previously demonstrated that the proliferative response to lipopolysaccharide (LPS) in cord blood mononuclear cells (CBMCs) is negatively correlated with the induced expression of interleukin (IL)-4. Our aim, therefore, was to examine whether an impaired cellular response to LPS in infancy is associated with the risk for asthma. Methods: In a prospective cohort study, the relationship between the CBMC response to LPS and the risk of atopy and wheezing after the age of 4 y was evaluated. results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Responsiveness of immune cells to infectious stimuli at birth is known to be highly variable between subjects. 31 Stronger neonatal cytokine responses, in particular for IFN-g, have been associated with reduced respiratory tract illness, [32][33][34] as well as with the incidence of wheeze, allergy, and asthma [11][12][13]35,36 later in childhood. In addition, lower expression levels of TLRs on cord blood immune cells has been linked to maternal allergy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Responsiveness of immune cells to infectious stimuli at birth is known to be highly variable between subjects. 31 Stronger neonatal cytokine responses, in particular for IFN-g, have been associated with reduced respiratory tract illness, [32][33][34] as well as with the incidence of wheeze, allergy, and asthma [11][12][13]35,36 later in childhood. In addition, lower expression levels of TLRs on cord blood immune cells has been linked to maternal allergy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, neonates born to parents with a history of allergy or asthma, who are themselves at an increased risk of experiencing these diseases, have lower mononuclear cell cytokine responses to respiratory syncytial virus 11 and lower mononuclear cell proliferative responses to LPS. 12 Additionally, direct comparisons with disease outcomes have shown that neonates who go on to have atopic disease or asthma have lower LPS-induced mononuclear cell proliferative responses 12 and lower cord blood serum levels of IL-4, TNF-a, and IFN-g. 13 Cells of the innate and adaptive immune systems express the vitamin D receptor, and their function is modulated by exposure to 1,25-dihydroxyvitamin D 3 (1,25[OH] 2 D 3 ) in culture. Direct in vitro treatment of innate immune cells with 1,25(OH) 2 D 3 has been shown to enhance the expression of antimicrobial peptides, such as cathelicidin, 14,15 and to influence innate immune signaling.…”
mentioning
confidence: 99%